Effect of elevated tool temperatures on the properties of high-strength aluminum alloys during tailor quench forming (TQF) - Rigas, Nikolaos; Jäckisch, Manuel; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers, Part B: Journal of Engineering Manufacture, 2022)
High-strength aluminum alloys have a great lightweight potential due to their high specific strength-to-weight ratio. However, industrial use of this material is limited due to the low formability at room temperature. In recent years, the so-called hot forming quench (HFQ®) process has proven, to be an effective forming method for manufacturing high-strength aluminum alloys. During deep drawing, the high cooling rate generates the potential for a subsequent aging operation and thereby the formation of strength-increasing precipitations. As a result, complex-shaped components with high strength can be produced. In the future, tailored components with both ductile and high-strength areas are increasingly needed to fulfill the growing lightweight and safety requirements of the government. One method to influence the mechanical properties is the use of a tailor quench forming (TQF) process. In this regard, a simultaneous component production and adjustment of the final mechanical properties is possible. However, it has not been investigated so far, how the tool temperature and the subsequent aging parameters influence the thermal interactions and thus the mechanical characteristics of the parts. In addition, the crash performance of these components has not been investigated. For this reason, a high-strength aluminum alloy is quenched under different thermal conditions and is then artificially aged. To determine the resulting thermo-mechanical properties, temperature analysis, hardness tests and tensile tests, as well as high-speed tests have been performe
Keywords: AA7075; Tailor quench forming; Mechanical properties; Crash performance